Genome sequence of the acid-tolerant Burkholderia sp. strain WSM2232 from Karijini National Park, Australia. Issue 3 (November 2014) - Walker, Robert; Watkin, Elizabeth; Tian, Rui; Bräu, Lambert; O'Hara, Graham; Goodwin, Lynne; Han, James; Reddy, Tatiparthi; Huntemann, Marcel; Pati, Amrita; Woyke, Tanja; Mavromatis, Konstantinos; et al.
Abstract Burkholderia sp. strain WSM2232 is an aerobic, motile, Gram-negative, non-spore-forming acid-tolerant rod that was trapped in 2001 from acidic soil collected from Karijini National Park (Australia) usingGastrolobium capitatum as a host. WSM2232 was effective in nitrogen fixation withG. capitatu m but subsequently lost symbiotic competence during long-term storage. Here we describe the features ofBurkholderia sp. strain WSM2232, together with genome sequence information and its annotation. The 7, 208, 311 bp standard-draft genome is arranged into 72 scaffolds of 72 contigs containing 6, 322 protein-coding genes and 61 RNA-only encoding genes. The loss of symbiotic capability can now be attributed to the loss of nodulation and nitrogen fixation genes from the genome. This rhizobial genome is one of 100 sequenced as part of the DOE Joint Genome Institute 2010 Genomic Encyclopedia forBacteria andArchaea -Root Nodule Bacteria (GEBA-RNB) project.